The effectiveness of birth ball exercise on the progression of the first stage of labor - Dera Sukmanawati; Ai Nurasiah; Indri Rismayanty Sudrajat (Palembang MediRose Publisher, 2024)
Background: Prolonged labor is a significant contributor to maternal mortality rates. Various interventions have been attempted to reduce the incidence of prolonged labor, including the use of the birth ball method.Objective: This study aimed to evaluate the impact of birth ball exercises on the progression of the first stage of labor.Methods: We employed a quasi-experimental design with a posttest-only control group. The sample consisted of 30 mothers giving birth at Cibingbin Primary Health Care, with each group containing 15 respondents selected through purposive sampling. Data were analyzed using the Mann-Whitney U test. Results: In the intervention group, all mothers experienced a normal progression of birth during the active phase of the first stage of labor, with an average labor duration of 5.70 hours. Conversely, in the control group, the majority (53.3%) experienced an abnormal progression of birth, with an average labor duration of 9.67 hours. The results indicated a significant difference in mean labor duration of 3.97 hours, demonstrating the birth ball’s effect on the progression of birth (p-value < 0.001).Conclusion: Birth ball exercises are a promising intervention for improving the progression of birth during childbirth. Therefore, these exercises can be implemented during normal labor. It is advisable that these exercises are supervised and guided by trained midwives or nurses.